2007
DOI: 10.1111/j.1601-183x.2007.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Animals lacking endothelin‐converting enzyme‐2 are deficient in learning and memory

Abstract: Endothelin‐converting enzyme (ECE)‐2 is a metalloprotease that possesses many properties consistent with it being a neuropeptide‐processing enzyme. This protease is found primarily in neural tissues, with high levels of expression in midbrain, cerebellum, hypothalamus, frontal cortex and spinal cord and moderate levels in hippocampus and striatum. To evaluate its role in neural function, mice have been generated lacking this enzyme. Physical appearance, autonomic reflexes, motor co‐ordination, balance, locomot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 46 publications
(54 reference statements)
0
60
0
Order By: Relevance
“…Processing of opioid peptides by ECE2 is likely to be of physiological significance as suggested by its distribution, which overlaps with the distribution of opioid peptide precursors such as proenkephalin (11,59), and its selective substrate specificity in processing opioid peptides (13). A previous study that analyzed the substrate specificity of ECE2 in vitro revealed that among the opioid peptides tested, Dyn B-13, BAM22, BAM18, and peptide E were selectively processed by ECE2 (13), and it is interesting to note that BAM22 and BAM18 were processed to yield BAM12 (13).…”
Section: Discussionmentioning
confidence: 99%
“…Processing of opioid peptides by ECE2 is likely to be of physiological significance as suggested by its distribution, which overlaps with the distribution of opioid peptide precursors such as proenkephalin (11,59), and its selective substrate specificity in processing opioid peptides (13). A previous study that analyzed the substrate specificity of ECE2 in vitro revealed that among the opioid peptides tested, Dyn B-13, BAM22, BAM18, and peptide E were selectively processed by ECE2 (13), and it is interesting to note that BAM22 and BAM18 were processed to yield BAM12 (13).…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for the neurophysiological screen, STFP, NORM, Morris water maze, fear conditioning, and FPS have been described previously (26,27). In pharmacology studies, mice were injected (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…WT and PC7 KO mice were indistinguishable on tests of gross sensory and motor performance (Table S3). Episodic memory, recollection of past events or experiences, was examined with the social transmission of food preference (STFP) and the novel object recognition memory (NORM) tests (26). To monitor STFP, a demonstrator mouse that ate a flavored diet was returned to its home cage to interact with its cage-mates.…”
Section: Pc7 Ko Mice Are Deficient In Episodic Memory and A Trkb Agonistmentioning
confidence: 99%
“…The ET-1/ECE-1/ET A pathway is essential for the development of pharyngeal arch-derived, craniofacial, and cardiac tissues (2,3), whereas the ET-3/ECE-1/ET B pathway is essential for the development of the enteric nervous system and skin melanocytes (4,5). Although Ece-2-null mice revealed no marked abnormalities (6), Ece-1/Ece-2 double mutants exhibited more severe cardiac abnormalities, including endocardial cushion defects (7). These molecular genetic studies point to the highly local action of ETs.…”
Section: Introductionmentioning
confidence: 99%